Accurate quantification of circular RNAs identifies extensive circular isoform switching events - Jinyang Zhang (Nature Portfolio, 2020)
Quantification and characterization of circRNAs in sequencing data remains challenging, hindering efforts to understand their roles and regulation. The algorithm introduced here enables accurate circRNA quantification and permits insight into competitive splicing between linear and circular isoforms.